Effect of Resveratrol on Leptin and Sirtuin 2 Expression in the Kidneys in Streptozotocin-induced Diabetic Rats - (:unkn) unknown (SCI PRINTERS & PUBL INC, 2015)
OBJECTIVE: To investigate the effect of resveratrol (RSV) on the histo pathology and leptin and sirtuin 2 expression levels of the kidneys in streptozotocin (STZ)-induced diabetic rats. STUDY DESIGN: The study was carried out with 33 young, healthy, female Wistar Albino rats. STZ was given (50 mg/kg, intraperitoneal, single dose) to the rats to induce and constitute a diabetes model. After 1 month of STZ, resveratrol (10 mg/kg) was given for 15 days. Then the kidneys were evaluated histo pathologically and the leptin and sirtuin 2 expressions were analyzed immunohistochemically. RESULTS: High glucose and fewer weight levels were seen in the STZ-induced diabetes mellitus group. The glucose levels in the RSV-administered diabetic group showed a tendency to decrease but not significantly. Decreased signs of histopathologic kidney damage was seen in the RSV-administered diabetic group, and an increased expression of leptin was seen in the diabetic kidney tissues. There were no significant differences of sirtuin 2 expression levels among the groups. CONCLUSION: It was observed that resveratrol caused changes in the diabetic kidney histology and leptin expression level. Resveratrol may be effective, with its antioxidant and antidiabetic effects, in the prevention of kidney damage caused by long-term hyperglycemia.
Keywords: diabetes mellitus; diabetic kidney disease; diabetic nephropathy; leptin; resveratrol; sirtuin 2; OXIDATIVE STRESS; NEPHROPATHY; PROGRESSION; PROTECTION; SECRETION; CYTOKINES; INSULIN; DISEASE; SIR2